The distribution of Co, Pb and Zn in the bottom sediment offshore of Kemaman, Terengganu, Malaysia during pre and post monsoon periods - Sevasamgaran, Syalindran; Mohamad Shazili, Noor Azhar; Yunus, Kamaruzzaman (Universiti Malaysia Terengganu, 2010)
This study focussed on heavy-metal concentrations in sediment off the coast of Kemaman. Sampling was conducted at 21 stations during the pre-monsoon and post-monsoon seasons. Sediment was analysed for total concentration of Co, Pb and Zn using ICP-MS after total acid digestion. The grain size of the sediment samples were measured by dry sieving and using a particle-size analyser. In addition, organic carbon content in the sediment was determined using the wet dichromate-oxidation method. The average concentration of Co, Pb and Zn during the pre-monsoon season was 11.40±3.84 lig/g dry weight, 44.08±33.40 [tg/g dry weight and 254.90±141.02 pg/g dry weight, respectively. The average concentration of Co, Pb and Zn during the post-monsoon season was 10.60±12.66 tig/g dry weight, 17.54±30.79 i.ig/g dry weight and 110.71±58.14 nig dry weight, respectively. Cu, Pb and Zn show poor correlation or negligible relationship with sediment particle size and organic carbon content. This study also found that all the elements have a mainly crustal origin rather than anthropogenic input with Geoaccumulation Index (Ivo) value of less than 1.0 and Enrichment Factors (EF) of 0.69-2.91which suggests minimal-to-moderate enrichment of the metals